Densidade de plantas agronômica ótima de soja para altas produtividades em ambiente subtropical - Balest, Darlan Scapini (2021)
The agronomic optimal plant density (AOPD) is the minimum number of plants needed to maximize grain yield in soybean crops. The aims of this work were: (i) to determine AOPD for different soybean maturity groups (MGs) in high yield sites and (ii) to determine AOPD for different sowing dates in high yield sites. To that end, 349 soybean fields were monitored and 21 experiments carried out at research stations and soybean fields, between the cropping seasons 2016/17 and 2019/20. Under irrigation, the plot with MG ≤ 5.5 presented AOPD equal to 30 plants m-², while the plots with 5.5 < MG < 6.5 and MG ≥ 6.5 presented reduction in AOPD of 14% (26 plants m-²) and 30% (21 plants m-²), respectively. Without irrigation, the plot with MG ≤ 5.5 presented AOPD equal to 29 plants m-², while the plots with 5.5 < MG < 6.5 and MG ≥ 6.5 presented reduction in AOPD of 34% (10 plants m-²). The AOPD values increased for early sowing (August) and late sowing (December and January) comparatively to the ideal sowing moment for MG = 5.0 (October). Grain yield increased for intermediate MGs (5.7 and 5.9) and late MGs (6.5 and 6.8) when lower plant densities were sowed in October and higher plant densities were sowed in August and January. The present study provides the AOPD values according to MG and sowing date in soybean crops grown under subtropical conditions.